Characterization of Polymorphic Forms of Rifaximin - Kogawa, Ana Carolina [UNESP]; Antonio, Selma Gutierrez [UNESP]; Nunes Salgado, Herida Regina [UNESP] (Aoac Int, 2016)
Rifaximin is a gut-selective oral antimicrobial that has no systemic adverse effects compared with placebo. It is used for the treatment of hepatic encephalopathy, traveler's diarrhea, irritable bowel syndrome, Clostridium difficile infection, ulcerative colitis, and acute diarrhea. The crystalline form present in rifaximin, a, has minimal systemic absorption compared to the amorphous form. The objective of this study was to obtain polymorphic forms of rifaximin using recrystallization processes. The forms were characterized and studied by thermal analysis, X-ray powder diffraction, scanning electron microscopy, and solubility testing. Six polymorphic forms of rifaximin, designated I VI, were obtained by the crystallization process by evaporation of the solvent. Some polymorphic forms obtained in this work may not have the same excellent tolerability as the reference medicine; therefore, studies such as these are extremely important and point to the need for greater requirements by the regulatory agencies overseeing polymorph analysis of the raw materials used in the manufacture of medicines marketed globally. These analyses are not required in the majority of official compendia. Partnerships among industries, research centers, and universities would be a viable way to consolidate research in this area and contribute to improving the quality of solid drugs.